2017
DOI: 10.1186/s12859-017-1568-1
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-high dimensional variable selection with application to normative aging study: DNA methylation and metabolic syndrome

Abstract: BackgroundMetabolic syndrome has become a major public health challenge worldwide. The association between metabolic syndrome and DNA methylation is of great research interest.ResultsWe constructed a binomial model to investigate the association between a metabolic syndrome index and DNA methylation in the Normative Aging Study. We applied the Iterative Sure Independence Screening (ISIS) method with elastic net penalty to DNA methylation levels at 484,548 CpG markers from 659 human subjects, and demonstrated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Methylation of the cg18181703 locus in the SOCS3 gene, involved in leptin and insulin signaling, was also identified in a separate study, inversely correlated with BMI, triglycerides, and MetS but positively correlated with HDL-c levels [ 24 ]. Relevant to our findings, Yoon et al independently identified ABCG1 (cg06500161) as being associated with MetS (in a Caucasian Veteran population) using an Iterative Sure Independence Screening analysis approach [ 30 ]. ABCG1 cg06500161 has also been reported to be associated with fasting insulin (in Caucasian non-diabetic adults) [ 26 ], blood lipids, and adiposity traits [ 29 , 31 ].…”
Section: Discussionsupporting
confidence: 72%
“…Methylation of the cg18181703 locus in the SOCS3 gene, involved in leptin and insulin signaling, was also identified in a separate study, inversely correlated with BMI, triglycerides, and MetS but positively correlated with HDL-c levels [ 24 ]. Relevant to our findings, Yoon et al independently identified ABCG1 (cg06500161) as being associated with MetS (in a Caucasian Veteran population) using an Iterative Sure Independence Screening analysis approach [ 30 ]. ABCG1 cg06500161 has also been reported to be associated with fasting insulin (in Caucasian non-diabetic adults) [ 26 ], blood lipids, and adiposity traits [ 29 , 31 ].…”
Section: Discussionsupporting
confidence: 72%
“…A recent study has also shown that the correlation between BMI and ABCG1 gene expression in monocytes is partially mediated by DNA methylation [ 31 ]. Previous studies have demonstrated that methylation of ABCG1 CpG sites cg06500161 and cg27243685 in the blood is positively associated with plasma triglyceride concentration and could be linked to obesity and metabolic syndrome [ 28 , 33 , 48 52 ]. One possible explanation is that ABCG1 could regulate the bioavailability and the subsequent activity of lipoprotein lipase (LPL), a rate-limiting enzyme that hydrolyzes circulating triglyceride-rich lipoproteins [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, methylation in the promoter region could enhance transcriptional inhibition, but the effect in gene region has not been conclusive [23]. As a metabolic disease interacting with environmental and genetic risks, T2DM was found to be associated with DNA methylation level changes at the whole genome [24] and CpG-labeled DNA methylation has also been found as a biomarker of metabolic syndrome [25]. At the same time, diabetes mellitus could lead to the change of the methylation level in specific tissues, such as adipose tissue, while the related differential genes are mainly related to cell cycle regulation and damage response [26].…”
Section: Discussionmentioning
confidence: 99%